COVID-19 HOAX DISINFORMATION DURING THE PANDEMIC IN INDONESIA - Riesta Ayu Oktarina; Muhajir Sulthonul Aziz; Fathul Qorib (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
Hoaxes related to Covid-19 continue to increase on social media in Indonesia. As one of the largest internet users in Indonesia, hoax production is predicted to continue to occur. This research wants to map the hoax of Covid-19 news, especially related to vaccine news in Indonesia. Data were obtained from the hoax buster page of the Committee for Handling Covid-19 and Aptika Kominfo from January 18 to May 28, 2021, as many as 36 hoaxes. This research is important to be a guide to understanding hoaxes so that anti-hoax activists can formulate effective hoax prevention strategies. The results of this study found that most of the hoaxes were related to misleading information about the impact of vaccines, found as many as 12 news stories spread through social media on Facebook, more specifically spreading distrust of the government. Other hoax themes are partly targeting some individuals who deliberately use the name of a doctor to provide misleading information. The covid-19 hoax that spreads a lot has a pattern of attach, sort, straighten, resettle, and break. That is, hoax makers make use of images or text from real events and then changed them according to certain intentions and purposes.